MODERN PEDAGOGICAL TECHNOLOGIES: TRANSFORMING LANGUAGE TEACHING FOR AGRICULTURAL STUDENTS - Shoynazarova Vazira Xo'shboqovna (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2024)
This study investigates the effectiveness of modern pedagogical technologies in enhancing language acquisition among agricultural students. Recognizing the pivotal role of language proficiency in the agricultural domain, the research explores the impact of interactive language learning platforms, virtual and augmented reality, online collaboration tools, mobile applications, and gamification on language teaching. The study aims to provide insights into how these technologies can be harnessed to tailor language instruction to the unique needs of agricultural education, fostering a more immersive and contextually relevant learning experience.